Socioeconomic status, social support, coping, and fear predict mental health status during the first year of the COVID-19 pandemic: A 1-year longitudinal study - Jarego, M.; Ferreira-Valente, A.; Sánchez-Rodríguez, E.; Miró, J.; Costa, P.; Pais-Ribeiro, J. (Current Psychology, 2024)
Research has shown that both the COVID-19 pandemic and the governmental measures implemented to tackle it severely impacted people’s mental health worldwide. This study aimed at monitoring adults’ mental health status during the first year of the COVID-19 pandemic and assessing demographic, socioeconomic, and psychosocial variables as mental health status development's potential predictors. A total of 105 adults (79% women; age: 18–72) completed a sociodemographic questionnaire and measures of mental health status, social support, coping, and fear of COVID-19 at T0 (Apr-May 2020), T1 (Nov 2020-Jan 2021) and T2 (May 2021). A Hierarchical Linear Model was used to assess the mental health status development trajectory and its predictors. Overall, no statistically significant differences in mental health status emerged. At the pandemic’s beginning, social support, and positive/active coping predicted better mental health status. Higher socioeconomic status, supportive coping, and the use of substances predicted poorer mental health status. Individuals who were more afraid of COVID-19 continued to improve their self-reported mental health status over time, although at a slower rate than individuals who were less afraid of COVID-19. These findings suggest that, in the context of an epidemiological crisis, such as COVID-19, fear of infectious disease should be assessed as a routine care measure, while cognitive behavioral interventions discouraging the use of supportive coping and the use of substances should be implemented.